The illustrated network : how TCP/IP works in a modern network - Goralski, Walter (ITpro collection, 2017)
With diagrams and screenshots, and end-of-chapter questions, this unique book presents an illustrated explanation on how TCP/IP works, using consistent examples from a working network configuration that includes servers, routers and workstations. --